Targeted metabolomics reveals fatty acid abundance adjustments as playing a crucial role in drought-stress response and post-drought recovery in wheat - Ullah, Safi; Khan, Mudassar Nawaz; Lodhi, Sumaira Salahuddin; Ahmed, Iftikhar; Tayyab, Muhammad; Mehmood, Tariq; Din, Israr Ud; Khan, Majid; Sohail, Quahir; Akram, Muhammad (Frontiers in Genetics, 2022)
Drought stress is one of the abiotic stresses restricting plant development, reproductive growth, and survival. In the present study, the effect of drought stress and post-drought recovery for the selected local wheat cultivar, Atta Habib, was studied. Wheat was grown for 16 days followed by drought stress for 7 days and allowed to recover for 7 days after the removal of the drought stress. Same-aged untreated plants were also grown as a control. The effect of drought stress and post-drought recovery on morphology (root length, shoot length, root weight, and shoot weight), enzymatic activity, and fatty acid profile were analyzed. The results showed that shoot weight (93.1 mg), root weight (85.2 mg), and shoot length (11.1 cm) decreased in the stressed plants but increased steadily in the recovered plants compared to the same-aged control plants, while root length showed a higher increase (14.0 cm) during drought stress and tended to normalize during the recovery phase (13.4 cm). The ascorbate peroxidase activity increased in the stressed plants (5.44 unit/mg protein) compared to the control, while gradually normalizing in the recovery phase (5.41 unit/mg protein). Gas chromatography coupled mass spectrometric analysis revealed abundance changes in important fatty acids, such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid. Palmitic acid (39.1%) and oleic acid (2.11%) increased in the drought-stressed plants, while a reduction in linoleic acid (6.85%) and linolenic acid (51.18%) was observed compared to the same-aged control plants, i.e., palmitic (33.71%), oleic (0.95%), linoleic (7.52%), and linolenic acid (55.23%). The results suggest that wheat tries to recover in the post-drought stage by repairing oxidative damage through ascorbate peroxidase, and by adjusting fatty acid abundances under drought stress and during the post-drought phase in an effort to maintain membranes’ integrity and a suitable fat metabolism route, thus helping recovery. Targeted metabolomics may be further used to explore the role of other metabolites in the drought-stress response mechanism in wheat. Furthermore, this relatively little explored avenue of post-drought recovery needs more detailed studies involving multiple stress durations.